A organização semântico-argumentativa do discurso : um estudo sobre as conexões entre enunciados - Malcorra, Bárbara Luzia Covatti (2018)
This research continues the studies developed in Argumentative Semantics, regarding the organization of the discourse meaning. For this purpose, it is taken as starting point the study by Graeff (2012), in which the author perceives the occurrence of two processes that connect utterances in texts: the process of similarity and contiguity. First process concerns the relationship between utterances that share the same internal argumentation, while the second process relates to the text thematic progression. Given the scarcity of studies focusing on these connections, it is necessary to extend these studies to a larger number of texts of different genres, in order to verify the operation of the described processes and the possibility of generalizing them to any text. In this perspective, based on the theoretical support of Theory of Argumentation within Language (ANL), especially in its version of the Theory of Semantic Blocks (TBS), this study aims to verify how the argumentative motives are organized for the constitution of the discourse meaning, and how the connections established between utterances allow making explicit the discourse global meaning. The corpus is composed of three chronicles published in the newspaper Zero Hora, and the methodology of analysis includes (a) the evocation of basic semantic units, that is, argumentative chains expressed in DC (therefore) or in PT (however); (b) the association to each of the chains evoked of the argumentative aspect of the semantic block they express; (c) the division of the texts into parts that express argumentative motives; (d) the identification of the connection established between the utterances; (e) the global meaning explanation of the discourse. It is verified not only occurrences of connections by contiguity and by similarity between utterances of the same part of the text, but also among different parts. Results suggest the possibility of explaining the thematic progression of the text from the perspective of Argumentative Semantics.